Hindu Marriage Law: Need, Impediments and Policy Guidelines - Syed Nadeem Farhat; Nadeem Farhat (Policy Perspectives, 2015)
Pakistan does not have a marriage law for Hindus. Customary law has been practiced to address issues among the community members. Law is needed to provide necessary documentation, standardization and provision of rights to every individual. Successive efforts for legislating upon Hindu marriages have been marred by intra-community differences on issues like divorce. An enduring change in mindset and recognition of the law among Hindu community asks for a comprehensive intra-community dialogue but mechanism for marriage registration needs to be devised through legislation without further delay.